THE ROLE OF LEADERSHIP IN IDENTIFYINGTHE OBSTACLES OF THE EMPLOYEE TO IMPROVE WORK MOTIVATION AT GOWA SOCIAL SERVICE OFFICE - Nurhaida; Riny Jefri (International Journal of Business English and Communication, 2023)
Leadership is a person's process of moving others by leading, guiding, and influencing them to do something to achieve the expected goals. Motivation is the desire that arises to move in order to achieve the desired goals. This study used a descriptive-qualitative method that aims to determine the role of leadership in identifying obstacles to increasing employee motivation at the Gowa social service office. The data collection techniques used in this study were observation checklists and interviews. The results of the study show that the role of leadership has been carried out optimally, namely by motivating employees through providing direction and guidance, establishing good communication, providing rewards and punishments, conveying clear information, and providing supervision and evaluation of employee performance. The obstacles faced by leaders are the difficulty in determining the form of motivation that will be given because employees have different characters and desires, as well as the lack of giving rewards to employees. The way leaders overcome these obstacles is to build cohesiveness and mutual respect.